Intact implicit statistical learning in borderline personality disorder. (September 2017) - Unoka, Zsolt; Vizin, Gabriella; Bjelik, Anna; Radics, Dóra; Nemeth, Dezso; Janacsek, Karolina
Abstract: Wide-spread neuropsychological deficits have been identified in borderline personality disorder (BPD). Previous research found impairments in decision making, declarative memory, working memory and executive functions; however, no studies have focused on implicit learning in BPD yet. The aim of our study was to investigate implicit statistical learning by comparing learning performance of 19 BPD patients and 19 healthy, age-, education- and gender-matched controls on a probabilistic sequence learning task. Moreover, we also tested whether participants retain the acquired knowledge after a delay period. To this end, participants were retested on a shorter version of the same task 24 h after the learning phase. We found intact implicit statistical learning as well as retention of the acquired knowledge in this personality disorder. BPD patients seem to be able to extract and represent regularities implicitly, which is in line with the notion that implicit learning is less susceptible to illness compared to the more explicit processes. Highlights: Extensive neuropsychological deficits have been identified in borderline personality disorder (BPD). No study has tested implicit learning in BPD yet. We used a probabilistic sequence learning task to measure implicit learning and retention. We found intact implicit statistical learning and retention of the acquired knowledge in BPD.